GLOSA DO WYROKU TRYBUNAŁU KONSTYTUCYJNEGO Z DNIA 14 GRUDNIA 2009 ROKU (SYGN. AKT K 55/07) - Poniatowski, Michał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Subject of the analysis in the article is the judgment of the Polish Constitutional Court of 14th December 2009. (signature act K 55/07). This sentence addresses the issue of public funding of three ecclesiastical universities in Poland (Pontifical Faculty of Theology in Warsaw, Pontifical Faculty of Theology in Wroclaw, Higher School of Philosophy and Education „Ignatianum” in Cracow). The Court found no violation of the Constitution by funding these schools with public funds. The article presents a synthesis of the arguments of the Court’s finding of no violation of the constitutional principle of impartiality of the public authorities in matters of religious belief, or in relation to outlooks on life or philosophical expressed in article 25.2 of the Constitution of 1997. Author of the article welcomed to this verdict and stated that it is necessary introduce a system of church financing higher education from public funds in Poland.